A Review of Carbon Monoxide Poisoning and Its Pathological Changes in Dogs and Cats - Sangary, Mohammad (Journal of Natural Sciences – Kabul University, 2022)
Carbon monoxide (CO) is an odorless, colorless, tasteless, and highly toxic gas. Undetectable by human senses, CO has long been regarded as a hazardous threat. It is produced during the incomplete combustion of hydrocarbon fuels and binds to hemoglobin (Hb) 200–300 times more readily than oxygen. CO penetrates the alveolar epithelium into lung capillaries, where it forms carboxyhemoglobin (COHb) by binding to Hb in red blood cells. The most recognized pathophysiological mechanism of acute CO poisoning is hypoxia, caused by impaired oxygen transfer due to COHb formation. CO poisoning results in severe damage to the brain and cardiac muscles. A distinguishing pathological feature of CO toxicity is bilateral lesions in the globus pallidus.